THE PHOTOMETRIC MODEL OF ARTIFICIAL SATELLITE AJISAI AND DETERMINATION OF ITS ROTATION PERIOD - Korobeynikova, E.; Koshkin, N.; Shakun, S.; Burlak, N.; Melikyants, S.; Terpan, S.; Strakhova, S. (Одеські астрономічні публікації, 2012)
Photometry is used to make remote diagnostics of an artificial satellite's motion around its centre of mass. Experimental satellite Ajisai was designed to explore the effects of the space factors, such as gravitation and magnetic fields, solar radiation and others, on its orbital motion and rotation. In the present study we consider the use of peculiar light curves of Ajisai, exhibiting a complex sequence of momentary flashes, for precise determination of the rotation period and velocity variations. For the first time, on the basis of the high-speed photometry, the model of placement of mirrors on the satellite's surface was designed to carry out further analysis of its kinematics.